Accelerating quality upgrading in Ugandan dairy value chains - Preliminary results from a value chain experiment - Ariong, Richard M.; Chamberlin, Jordan; Kariuki, Sarah Wairimu; Van Campenhout, Bjorn (International Food Policy Research Institute, 2024)
Uganda’s dairy sector faces persistent challenges in milk quality, particularly low butterfat and solids-not-fat (SNF) levels. This study uses a multilevel randomized control trial with interventions at both Milk Collection Center (MCC) and farmer levels to identify some of the barriers that prevent quality upgrading within dairy value chains. Innovations included milk analyzers, digital record-keeping, and farmer-focused educational campaigns.